1995
DOI: 10.1007/bf00041121
|View full text |Cite
|
Sign up to set email alerts
|

Studies of cotyledon protoplast cultures from B napus, B. campestris and B. oleracea. II: Callus formation and plant regeneration

Abstract: Cotyledons from twelve cultivars ofBrassica; B. napus (Westar, Eureka, Global, Pivot and Narc 82); B. campestris: (Arlo, Sonja, Bunyip and Wonk Bok) and B. oleracea (Phenomenal Early, Sugar Loaf and Earliball) were used for protoplast isolation and culture in a comparative study of cell colony and callus formation, and plant regeneration. The formation of cell colonies and callus from protoplast cultures were significantly influenced by the light conditions of seed germination. All twelve cultivars showed cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…Differentiation in the in vitro cultures is generally known to be genotype-specific, and Brassica species are no exception (Jourdan and Earle 1989; Loudon et al 1989; Zhao et al 1995; Hansen et al 1999a), as confirmed in this study. Mesophyll- and hypocotyl-derived protoplasts were successfully isolated with satisfactory yields, viability, and division frequencies, especially for the red form of cabbage cv.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Differentiation in the in vitro cultures is generally known to be genotype-specific, and Brassica species are no exception (Jourdan and Earle 1989; Loudon et al 1989; Zhao et al 1995; Hansen et al 1999a), as confirmed in this study. Mesophyll- and hypocotyl-derived protoplasts were successfully isolated with satisfactory yields, viability, and division frequencies, especially for the red form of cabbage cv.…”
Section: Discussionsupporting
confidence: 81%
“…The cytoplasmic male sterility system has been introduced to B. oleracea through asymmetric protoplast fusion (Sigareva and Earle 1997). Positive results, as mentioned above, have been achieved using B. oleracea accessions that were selected for high plant regeneration capacity, but the ability to undergo meiotic divisions and regenerate shoots remained problematic (Jourdan and Earle 1989; Zhao et al 1995; Hansen et al 1999a). Although intensive screening of protoplast culture conditions has been performed, the effects of genotype have still overridden most efforts to improve protocols for plant regeneration from protoplast culture.…”
Section: Introductionmentioning
confidence: 99%
“…Brassica oleracea is a plant species that includes many common foods such as cabbage, broccoli, kale, kohlrabi, and cauliflower. The extensive screening of protoplast culture in B. oleracea showed that the effect of genotype overrides the wide use of protoplast techniques in the breeding and biotechnology of this species (Jourdan et al 1990;Kik and Zaal 1993;Zhao et al 1995;Adamus 2012, 2014); therefore, improvements in the methodology aiming to increase the mitotic activity of cultured protoplasts and plant regeneration are needed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, protoplasts, cells lacking a cell wall, are fragile and sensitive to changes in culture conditions. However, there have been relatively few studies on the effects of light on donor tissues used for protoplast isolation (Zhao et al 1995, Geng-Guang 1996. The effect of light on cell wall structure and chemical composition has been reported however (Parvez et al 1996).…”
Section: Keskitalo M Protoplast Production From In Vitro Cultured Smentioning
confidence: 99%